Dinamika Perilaku Indisipliner dan Strategi Guru Sosiologi di SMA Negeri 1 Sukoharjo: Dynamics of Indisciplinary Behavior and Strategies of Sociology Teachers at SMA Negeri 1 Sukoharjo - Azizah, Hana Nur; Astutik, Dwi; Purwanto, Danang (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
This article aims to examine acts of indiscipline among students at SMA Negeri 1 Sukoharjo by exploring their causes and effects, and identifying effective control strategies based on social control theory. Utilizing a qualitative methodology within a case study approach, the data for this article were obtained through observation and structured interviews with sociology teachers, the principal, and other supporting informants. The findings indicate that student indiscipline is influenced by a variety of factors, including self-awareness, the family and school environments, and social interactions. The acts of indiscipline encompass a range of behaviors, from truancy to non-compliance with school rules. Moreover, the implemented control strategies, which emphasize the development of strong social bonds between students and their environment, have proven effective in reducing incidents of indiscipline. The study concludes that strengthening social bonds through attachment, commitment, involvement, and belief is essential in preventing and controlling indiscipline among students. It highlights the significance of active roles for teachers and school authorities in the processes of character building and discipline. Abstrak Artikel ini bertujuan untuk mengkaji tindakan indisipliner di kalangan siswa SMA Negeri 1 Sukoharjo, menyelidiki penyebab dan dampaknya, serta mengidentifikasi strategi pengendalian yang efektif berdasarkan teori kontrol sosial. Menggunakan metode kualitatif dengan pendekatan studi kasus, data dalam artikel ini diperoleh melalu observasi dan wawancara terstruktur dengan guru sosiologi, kepala sekolah, dan narasumber pendukung lainnya. Hasil kajian ini menunjukkan bahwa perilaku indisipliner siswa dipengaruhi oleh berbagai faktor, termasuk kesadaran diri, lingkungan keluarga dan sekolah, serta pergaulan. Tindakan indisipliner siswa mencakup berbagai perilaku, dari membolos hingga tidak mengikuti aturan sekolah. Lebih lanjut, strategi pengendalian yang diterapkan, yang menekankan pada pembangunan ikatan sosial yang kuat antara siswa dengan lingkungannya, terbukti efektif dalam mengurangi insiden perilaku indisipliner. Kajian ini menyimpulkan bahwa penguatan ikatan sosial, melalui kelekatan, komitmen, keterlibatan, dan kepercayaan, merupakan kunci utama dalam mencegah dan mengendalikan tindakan indisipliner di kalangan siswa, serta pentingnya peran aktif guru dan pihak sekolah dalam proses pembinaan karakter dan disiplin siswa.